IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENANAMKAN NILAI KARAKTER PADA SISWA KELAS IV DI SDN ROWOREJO - Aini Munawaroh Nurd; Yuli Widiyono; Suyoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this study are: 1) To determine the form of implementation of the Pancasila Student Profile Strengthening Project (P5) in instilling character values ​​in grade IV students of SDN Roworejo, 2) To determine the character values ​​of students through the implementation of the Pancasila Student Profile Strengthening Project (P5) in grade IV students of SDN Roworejo, 3) To determine the supporting and inhibiting factors in the implementation of the Pancasila Student Profile Strengthening Project (P5) in grade IV students of SDN Roworejo. This study uses a qualitative descriptive research method. The subjects of this study were grade IV teachers and grade IV students consisting of 14 students. Data collection techniques used interviews, observations, and documentation. Data validity used president observation, source triangulation, method triangulation, and peer discussion. Data analysis used data collection, data reduction, data presentation, and verification. The results of this study are 1) The form of P5 activities is mutual cooperation and creativity with the theme of local wisdom in making jumputan batik. 2) Students are directly involved in making jumputan batik. Through the project of making jumputan batik, researchers observed character values ​​in students such as mutual cooperation and creativity. 3) Supporting factors for the implementation of P5 include adequate facilities, support from schools, teachers and students, and enthusiasm from students. While the inhibiting factors for the implementation of P5 include challenges in the form of a lack of basic batik skills from teachers and requiring a long time.